Transient liquid-phase assisted spark-plasma sintering and dry sliding wear of B4C ceramics fabricated from B4C nanopowders. Issue 3 (March 2021) - Ojalvo, Cristina; Zamora, Victor; Moreno, Rodrigo; Guiberteau, Fernando; Ortiz, Angel L.
Abstract: With the motivation of developing B4 C composites with superior wear resistance for tribological applications, an ultrafine-grained (∼200−300 nm) B4 C composite was fabricated, characterized microstructurally, and tested mechanically and tribologically. First, a well-dispersed powder mixture of B4 C nanopowders (∼40 nm) with coarse Ti-Al powders (∼38 μm) as transient liquid-phase sintering additives was environmentally-friendly prepared by aqueous colloidal processing, optimized by measurements of the zeta potential of dilute suspensions and rheological studies of concentrated suspensions. Second, the powder mixture obtained by freeze-drying was densified by spark-plasma sintering (SPS), identifying the optimal SPS temperature (1850°C) by measurements of density, hardness, and toughness. Third, the dry sliding-wear behaviour of the optimal superhard B4 C composite (∼31.5 GPa) was investigated by pin-on-disk tests and observations of the worn surface, determining its specific wear rate (∼4.4·10 −8 mm³/(N·m)) as well as wear mode (two-body abrasion) and mechanism (plastic deformation). And lastly, the wear behaviour of the ultrafine-grained B4 C composite was compared with that of a reference fine-grained (∼0.7−0.9 μm) B4 C composite, finding that both have the same mode and mechanism of wear but with the former being more resistant than the latter (∼2.3·10 7 vs 1.9·10 7 (N·m)/mm³). Implications for the fabrication of B4 C tribocomponents with greater superior wear resistance are discussed.